Changes in Heart Rate Variability Recorded in Natural Situation with T-Shirt Integrated Sensors and Level of Observed Behavioral Excitation: A Pilot Study of Patients with Intellectual Disabilities and Psychiatric Disorders - Palix, Julie; Akselrod, Michel; Cungi, Charly; Giuliani, Fabienne; Favrod, Jérôme (Frontiers in Psychiatry, 2017)
Background: The present study investigates the possibilities of using heart-rate variability (HRV) parameters as physiological markers that precede increase in observed behavioral excitation of intellectually disabled individuals. The ability to recognize or predict such patterns, especially in patients showing unpredictable reactions and language deficiencies, might be a major step forward in clinical research. Method: Thirteen volunteers with intellectual disabilities, who had suffered of at least one event of overt aggression in the preceding three months, participated to the study. The protocol consists in the acquisition of continuous electrocardiogram (ECG) throughout approximately two times of 8 hours in natural situation, using a t-shirt integrated with sensors . Simultaneously, an observer evaluates the patient’s level of overt excitation from calm (level 1) to extremely tense (level 5) and send online via Bluetooth these triggers into the ECG signals. The HRV indexes were then estimated offline on the basis of the inter-beat intervals recorded by the ECG, independently for the 30 minutes preceding each behavioral tension marking point, averaged, and compared through nonparametric Wilcoxon matched-pairs test. Of these, the RMSSD and LF/HF calculations were used to observe the fluctuations of inhibitory activity and cardiovagal balance through different tension states. Results: Seven individuals have sufficient reliable data for analysis. They have reached at least a level 3 of behavioral excitation (moderately tense) or more (very to extremely tense, level 4 and 5), and have been retained for further analysis. In sum, a total of 197 periods of tension were kept, made up of 46 periods of slight excitation (level 2), 18 of moderate excitation (level 3), 10 of high excitation (level 4) and 5 of extreme agitation (level 5). Variations in the HRV as a function of degree of excitation are observed for RMSSD index only (inhibitory parasympathetic activity). The changes from calm to increasing levels of excitation are characterized by a significant downfall in RMSSD index when patients were evaluated to be in a very high level of tension (level 4). Conclusion: The presence of precursors to agitation, reflected in the falling-off of parasympathetic activity, offers potentially interesting prospects for therapeutic development.